Development of Competencies in English Classes as Per International Assessment Program Standards - qizi, Gulbahor Komilova Abdumuxtor (PT. Antis International Publisher, 2024)
English language competency is crucial in today's globalized world. As a result, international assessment programs have been established to measure and benchmark students' English language skills. International programs set standards and guidelines that serve as a reference for educators in designing their English language curriculum and instructional practices. This article explores the development of competencies recorded in the standards of international assessment programs within English classes.